High Pressure and Standard Photoelectron Spectroscopy of Materials for Hydrogen Storage and Production - Ryder, Christopher P. C. (2024)
It is widely agreed that hydrogen, a clean, renewable fuel which produces only water as a by-product when reacted with oxygen in air, can and must be used to replace fossil fuels for applications across all sectors if global targets for greenhouse gas emission reductions are to be met, and the harmful effects of the climate crisis are to be mitigated and reversed. However, many of the technologies associated with the lifecycle of truly green hydrogen are still in their infancy. Production still relies heavily on fossil fuels, and electrolysis alone cannot be expected to cover the entire capacity required for their replacement, while the storage of hydrogen commonly uses very high-pressure compression (up to 700 bar) with large associated costs and safety concerns. This thesis therefore looks to investigate materials which may provide alternative methods in each case, namely solar water splitting photocatalysed by titanium dioxide for production, and solid-state storage of hydrogen in intermetallic compounds.